Reflective practice in speech-language pathology: A scoping review. (August 2015) - Caty, Marie-Ève; Kinsella, Elizabeth Anne; Doyle, Philip C.
Abstract Purpose: Within the profession of speech-language pathology, there is limited information related to both conceptual and empirical perspectives of reflective practice. This review considers the key concepts and approaches to reflection and reflective practice that have been published in the speech-language pathology literature in order to identify potential research gaps. Method: A scoping review was conducted using Arksey and O'Malley's (2005) framework. Result: A total of 42 relevant publications were selected for review. The resulting literature mapping revealed that scholarship on reflection and reflective practice in speech-language pathology is limited. Our conceptual mapping pointed to the use of both multiple and generic terms and a lack of conceptual clarity about reflection and reflective practice in speech-language pathology. Two predominant approaches to reflection and reflective practice were identified: written reflection and reflective discussion. Both educational and clinical practice contexts were associated with reflection and reflective practice. Publications reviewed were primarily concerned with reflection and reflective practice by novices and expert practitioners. Conclusion: Based on this review, we posit that there is considerable need for conceptual and empirical work with a goal to support university- and work-based educational initiatives involving reflection and reflective practice in speech-language pathology.